Sustainable coffee supply chain management: A case study in Buon Me Thuot City, Daklak, Vietnam - Giang N. T. Nguyen; Tapan Sarker (International Journal of Corporate Social Responsibility (JCSR), 2018)
This paper aims to analyze and discuss the evolution towards sustainable coffee supply chain and its management in Vietnam. Coffee is a major agricultural export commodity of Vietnam with the export value accounts for 3% of national GDP in 2014 and provides a livelihood for approximately 2.6 million people. However, the sector is facing enormous challenges as the current farming methods and processing infrastructure have been unsustainable resulting in many catastrophic impacts on the environment such as deforestation and soil degradation that have the potential to lead to a decrease in the quality of coffee beans. Using a case study in Buon Me Thuot City, Daklak, Vietnam, the paper analyses the key factors influencing the sustainable coffee supply chain management in Vietnam. Our analysis confirms that although productivity is high, and farmers have positive experiences in this sector, sustainability issues are emerging. For instance, the farmers have experienced soil erosion and a lack of water and as such are now more willing to incorporate sustainability initiatives in their production and processing.
Keywords: 650; Coffee supply chain; Sustainability; Case study; Vietnam